Effects of feeding frequency on growth performance of endangered Temoleh, Peobarbus jullieni (Sauvage, 1880) juveniles - Zakaria, M. Hazmadi; Harmuj Ali Sarker, S. M. Nurul Amin; Arshad, Aziz; Rahman, Md. Aminur; Christianus, Annie; Nor Azrie, M. Z. (Triveni Enterprises, 2016)
The experiment was designed to investigate the effects of feeding frequencies on the growth and feed utilization efficiencies of endangered Temoleh, Probarbus jullieni under captive rearing condition. The juvenile fish, weighing from 12.03g to 32.64g, were fed with an extruded commercial pellet for 60 days. Three restricted feeding regimes were tested in treatments viz., three meals per day (Teratment-1, T1), two meals per day (Teratment-2, T2) and one meal per day (Teratment-3, T3). The experiment was carried out in aquarium tanks on a recirculating water system. The fortnightly mean growth rate was 2.00 g in T1, 1.27 g in T2 and 0.57 g in T3, decreasing from T1 to T3 in that order. The percentage weight gain, specific growth rate (SGR), and daily growth rate (DGR) were significantly different (P < 0.05) among the treatments, which were highest in T1 as compared to those in T2 and T3, respectively. The best food conversion ratio (FCR) was also observed in T1. Among the tested treatments, three times a day feeding regime appeared to be the most suitable and could be recommended for rearing of P. jullieni under intensive culture systems.